Rancang Bangun Tripod Kamera Otomatis Pengikut Objek Menggunakan Sensor Ultrasonik - Ali Irvan; Wildian Wildian (Universitas Andalas, 2023)
A design of an object follower automatic tripod camera based on an ultrasonic sensor has been done. The object follower automatic tripod camera design consists of 3 units of ultrasonic sensor, a servo motor, and an Arduino Uno microcontroller. An ultrasonic sensor was used to detect an object in the left front, in front, and in the right front of the device. Object detection was performed by using distance intervals from sensors. The sensors were designed to make 30° angle intervals each other and make 90° total angle detection in front of the device. Characterization of ultrasonic sensors showed that sensors could detect an object with an angle of 15°. The servo test shows that it can rotate until 160°. Servo could rotate until the angle position at 60°, 90°, and 120°. Device testing shows that it was able to detect an object at a distance of 2 m and a total angle of 90° in front of the device, and the servo was able to rotate the camera to the detection field.